2003
DOI: 10.1007/s00213-002-1287-8
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of MPEP, an mGluR5 antagonist, and memantine, an N-methyl-D-aspartate receptor antagonist, on morphine antinociceptive tolerance in mice

Abstract: The data suggest that both mGluR5 and NMDA receptors may be involved in the development of morphine antinociceptive tolerance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
34
1
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 44 publications
7
34
1
1
Order By: Relevance
“…A functional interactions between mGluR5 and NMDAR is well supported by the literature (Salter and Kalia, 2004) and our own data (Jia et al, 1998;Huang et al, 2001;Hannan et al, 2001). Indeed, several observations have shown that agonists and antagonists of mGluR5 may, respectively, attenuate and potentiate the effects of NMDAR antagonists in vivo (Kozela et al, 2003;Kinney et al, 2003;Homayoun et al, 2004). As mGluR5 antagonist administered alone could not disrupt PPI, but could enhance the effects of PCP (Kinney et al, 2003), it is possible that the PPI deficit in mGluR5 mutants might result from an interaction between NMDAR hypofunction together with missing mGluR5 complex rather than the alternative of only a parallel pathway downstream of mGluR5.…”
Section: Discussionsupporting
confidence: 61%
“…A functional interactions between mGluR5 and NMDAR is well supported by the literature (Salter and Kalia, 2004) and our own data (Jia et al, 1998;Huang et al, 2001;Hannan et al, 2001). Indeed, several observations have shown that agonists and antagonists of mGluR5 may, respectively, attenuate and potentiate the effects of NMDAR antagonists in vivo (Kozela et al, 2003;Kinney et al, 2003;Homayoun et al, 2004). As mGluR5 antagonist administered alone could not disrupt PPI, but could enhance the effects of PCP (Kinney et al, 2003), it is possible that the PPI deficit in mGluR5 mutants might result from an interaction between NMDAR hypofunction together with missing mGluR5 complex rather than the alternative of only a parallel pathway downstream of mGluR5.…”
Section: Discussionsupporting
confidence: 61%
“…For example, there is an interaction between mGlu5 and NMDA receptor antagonists on morphine antinociceptive tolerance (Kozela et al, 2003), phencyclidine-induced hyperlocomotion, and disruption of prepulse inhibition (Henry et al, 2002;Kinney et al, 2002Kinney et al, , 2003. Together with the present data, these studies suggest that selective modulation of glutamatergic transmission through mGlu5 receptors can be used as a pharmacological strategy for the treatment of brain disorders that involve NMDA receptor dysfunction.…”
Section: Discussionsupporting
confidence: 61%
“…The selective mGlu5 receptor antagonist 2-methyl-6-(phenylethynyl)-pyridine (MPEP) blocks NMDA-induced membrane depolarization in striatal spiny neurons and in cortical wedges (Pisani et al, 1997;Attucci et al, 2001). Systemically administered mGlu5 and NMDA receptor antagonists produce similar anxiolytic (Spooren et al, 2000;Chojnacka-Wojcik et al, 2001), neuroprotective (Bruno et al, 2000), anticonvulsant (Chapman et al, 2000), and tolerance blocking (Kozela et al, 2003) effects, and disrupt prepulse inhibition (Henry et al, 2002;Kinney et al, 2002). Therefore, modulation of mGlu5 receptors may be an effective therapeutic strategy for manipulation of NMDA receptor-mediated neurotransmission in disorders such as schizophrenia (Tamminga, 1998;Goff and Coyle, 2001; Krystal et al, 2003;Moghaddam, 2003) and addiction (Wolf, 1998), where NMDA receptor dysfunction is suspected.…”
Section: Introductionmentioning
confidence: 99%
“…This functional coupling could result from the postsynaptic association of NMDA receptors with a complex of proteins, which includes different scaffolding proteins (eg PSD-95, Homer, Shank), but other receptors including mGluR5 are also linked to this complex (Kotecha et al, 2003), and activation of mGluR5 can lead to an enhancement of NMDA receptor function through phosphorylation by protein kinase C (Hermans and Challiss, 2001;Schoepp and Conn, 1993). The high affinity of MPEP for mGluR5 receptors, which is more than 1000-fold higher compared to NMDARs, makes it very unlikely that under the used conditions MPEP affects NMDARs directly (Oleary et al, 2000;Gubellini et al, 2001;Spooren et al, 2001;Kozela et al, 2003). In summary, the functional coupling of mGluR5 and NMDA receptor suggests that the blockade of mGluR5 by MPEP reduces glutamatergic signaling through NMDA receptors and thereby interacts with ethanol-seeking and relapse behavior.…”
Section: Discussionmentioning
confidence: 99%